Optical identification of few layers of MoS₂, MoSₑ₂, WS₂ and WSₑ₂ - G, Munkhsaikhan; R, Buyanjargal; B, Odontuya; D, Otgonbayar; D, Naranchimeg; L, Sarantuya; /n, Tuvjargal (Scientific transaction of the National University of Mongolia. Physics, 2022)
We propose a study to identify mono- and few-layers of molybdenum disulfide, molybdenum diselenide, tungsten disulfide, and tungsten diselenide. The number of layers is determined by optical microscopy. The single and few layers of the transition metal dichalcogenides transferred onto SiO2/Si substrates. SiO2/Si substrates with 270 nm thickness SiO2 have been shown to provide high optical contrast, enabling optical identification of the transition metal dichalcogenides easier.